STRATEGI PENGELOLAAN BADAN USAHA MILIK DESA LOREJO BAKUNG BLITAR DALAM MENINGKATKAN PENDAPAN ASLI DESA - Siswahyudi (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2025)
This study analyses the management strategy of the Mekar Arum Village-Owned Enterprise (BUMDes) in Lorejo Village, Bakung Subdistrict, Blitar Regency, with the aim of increasing Village Original Income (PADes) and the welfare of the village community. In this context, BUMDes acts as a driver of the local economy by productively managing the village's natural and human resources. This study adopts a qualitative case study approach with data collection techniques through in-depth interviews, participatory observation, and document studies involving BUMDes administrators, village governments, and the community. The main focus of this study is to evaluate the effectiveness of the strategies implemented in BUMDes management and their impact on increasing PADes and community empowerment. The results show that although BUMDes Mekar Arum has successfully launched several business units, such as a village market and clean water management, its effectiveness is hampered by limited human resources, weak planning, and suboptimal financial management. The evaluation shows that there are administrative constraints and a lack of technical skills among BUMDes administrators, which hinder the maximum implementation of the programme. These findings emphasise the importance of more systematic planning, continuous training for administrators, and improved coordination between business units in order to achieve sustainable growth. The novelty of this research lies in its attempt to fill the research gap on BUMDes management strategies in areas that have not been widely studied, particularly in Mekar Arum Village, which has different characteristics and challenges from other villages. This research provides important insights into how BUMDes can play a role in village economic development with a more planned approach based on strengthening human resource capacity and transparent and accountable management.